(untitled) (Terr@ Plural, 2023)
Shales constitute a recent frontier of studies in Sedimentary Geology, stimulated by the new exploratory panorama of Shale Gas, despite being the sealant of many petroleum systems. However, in Brazil, the generation of natural gas associated with paleontological studies is unprecedented and fundamental for determining the real regional potentialities in a process of advancing scientific and technological knowledge. Taphonomic studies of fossil macrofauna and ichnology are integrated with sedimentological data, expanding the capacity for paleoenvironmental interpretation of the sedimentary facies. Samples from three distinct outcrops in the Campos Gerais region of the state of Paraná were analyzed and two tafofauna and three ichnofauna were identified: Skolithos, archetypical and distal Cruziana. The paleontological analyses proposed here provide support for biostratigraphic correlations, paleoenvironmental and paleoecological interpretations of the outcrops prospected, assisting in the evaluation of the quality of the shales of the Ponta Grossa Formation from the point of view of hydrocarbon generation.